Epidemiological Analysis Of Breast Cancer And The Effectiveness Of Radiation And Chemotherapy (Texas Journal of Medical Science, 2026)
This article The article presents a clinical and epidemiological analysis of breast cancer (BC) among women in the Fergana region, assessing the prevalence of the disease, the effectiveness of radiation and chemotherapy, as well as the frequency and nature of therapeutic consequences. This study used data from 382 patients treated at the Fergana Regional Branch of the Republican Specialized Scientific and Practical Medical Center of Oncology and Radiology from 2020 to 2024. Radiation therapy demonstrates a higher survival rate (76.4%), which is explained by its use primarily in stages I and II, local tumor control, and a reduced risk of recurrence. Chemotherapy (72.1%) is used more often in stage III, HER2+, and triplenegative forms. Therefore, a slight decrease in survival is explained by the initially more severe clinical profile of the group, rather than by the lower efficacy of the method. Key prognostic factors, survival rates, and the frequency of side effects of therapy are identified.